Prioritization of R&D projects in the aerospace sector: AHP method with ratings - Mischel Carmen N. Belderrain; Francisco Carlos M. Pantoja; Amanda C. Simões da Silva (Journal of Aerospace Technology and Management, 2010)
The prioritization of R&D projects in the Aerospace Sector is considered a complex problem because it involves qualitative and quantitative issues that are frequently conflicting. This paper aimed to apply the AHP (Analytic Hierarchy Process) method with ratings to select projects of R&D in a Brazilian aerospace institution, Department of Science and Aerospace Technology (DCTA). The results showed that using ratings is appropriate when there is a great quantity of projects, since it reduces the judgments required to the decision maker.